HOW QUALITY OF WORK LIFE FOSTERS NURSE COMMITMENT: JOB SATISFACTION AS AMEDIATOR FROM A SPILLOVER VIEW - Veronika Agustini Srimulyani; Citra Rumaisa; Yustinus Budi Hermanto (FAKULTAS EKONOMI DAN BISNIS UNIKARTA, 2026)
To improve patient perceptions of care quality and ensure adequate nursing staff availability, attention to nurse job satisfaction and nurse organizational commitment is crucial. Nurse quality of work life is one factor that hospital management must consider to improve job satisfaction and organizational commitment. This empirical study evaluates and examines the impact of nurses' perceived quality of work life on nurses’ job satisfaction and nurses’ organizational commitment using a spillover theory perspective. The study’s participants were103 inpatient nurses from the Regional General Hospital (RSUD) dr. Sayidiman in Magetan, East Java, Indonesia. Path analysis and the online Sobel test are the data analytic methods utilized to evaluate the hypothesis. The findings demonstrate that nurses’ job satisfaction may be greatly raised by a high quality of work life, and that job satisfaction in turn greatly raises organizational commitment. The study’s findings demonstrate that among RSUD dr. Sayidiman Magetan’s inpatient nurses, job satisfaction serves as a perfect mediator between quality of work life and organizational commitment. Academically, this study expands Spillover Theory and Social Exchange Theory by proving that organizational investments in workplace quality do not directly bind employee loyalty unless they successfully foster immediate job satisfaction first.